KUALITAS PELAYANAN POSYANDU REMAJA DI KELURAHAN PONDOK KOPI KECAMATAN DUREN SAWIT KOTA JAKARTA TIMUR - , Ummul Khair (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The Youth Integrated Health Post (Posyandu Remaja) in Pondok Kopi Subdistrict strives to improve adolescent health and provide education; however, it faces challenges such as a lack of facilities and infrastructure that may affect service effectiveness. Service quality is closely related to the competence of the cadres, while active adolescent participation is key to success. This research analyzes the dimensions of physical evidence, reliability, responsiveness, assurance, and empathy of the Youth Integrated Health Post, identifying facility issues, service reliability, and obstacles to adolescent participation. Recommendations include adding facilities, expanding space, enhancing cadre training, and further efforts to increase adolescent participation, with the hope of advancing the quality of public services provided by the Youth Integrated Health Post and supporting the health and well-being of adolescents in the Pondok Kopi community. This study employs a qualitative analysis method focusing on the five dimensions of the Youth Integrated Health Post services in Pondok Kopi Subdistrict: physical evidence, reliability, responsiveness, assurance, and empathy. In-depth interviews were conducted with stakeholders, including adolescents, cadres, and health officers, to identify key issues and improvement opportunities. The analysis results provide a holistic overview of the Youth Integrated Health Post's conditions, serving as a foundation for constructive recommendations. This method is designed to provide a profound understanding of service quality and create a basis for constructive improvements in enhancing the impact of the Youth Integrated Health Post in the Pondok Kopi community.